1993
DOI: 10.1016/0020-7292(93)90516-y
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal sonographic features in diagnosis of ectopic pregnancy

Abstract: The results of this study indicate that TVS can help to facilitate the diagnosis of EUP in most cases. EUP can be confidently diagnosed by demonstration of adnexal ring, and excluded by visualization of intrauterine sac. Complex adnexal mass and echogenic fluid are extremely helpful in making the diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 12 publications
0
20
2
Order By: Relevance
“…21 Previous sonographic studies have reported echogenic or "particulate" fluid in 25 to 57% of ectopic pregnancies. 7,16,[22][23] The higher rate in this study likely reflects the selected patient population. Although not specifically studied prior to this study, echogenic fluid has correlated with hemoperitoneum.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…21 Previous sonographic studies have reported echogenic or "particulate" fluid in 25 to 57% of ectopic pregnancies. 7,16,[22][23] The higher rate in this study likely reflects the selected patient population. Although not specifically studied prior to this study, echogenic fluid has correlated with hemoperitoneum.…”
mentioning
confidence: 90%
“…Free pelvic fluid has been shown to carry a risk for ectopic pregnancy, with echogenic fluid much more worrisome in patients referred with a clinical suspicion. [5][6][7][8][9][15][16][17] Accurate characterization of pelvic fluid requires adequate gain setting. Too high gain settings can create artifactual echoes in anechoic fluid, and too low settings can cause echogenic fluid to appear anechoic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations